Pengaruh Lokasi Dan Fasilitas Terhadap Loyalitas Pelanggan Di Cafe Vizie Lahat - Yova Herliza; Rudi Eduar; Hestin Hestin (Jurnal Multidisiplin Dehasen (MUDE), 2026)
This study aims to determine the Influence of Location and Facilities on Customer Loyalty at Cafe Vizie Lahat either partially or simultaneously. This study is a quantitative associative research using the Accidental Sampling technique with the slovin formula method in determining samples. The sample used in this study amounted to 77 customers who were used as research respondents. Based on the results of the study, the regression equation Y = 6.549 + 0.408 X1 + 0.431 X2 + e, means that without the variables Location (X1) and Facility (X2), Customer Loyalty (Y) is 6.549. The value of the determination coefficient (R2) is 0.764, meaning that the independent variables have a contribution with the dependent variable of 76.4% and the remaining 23.6% are influenced by other factors that were not studied by the author. Based on the results of SPSS processing version 25.0, the Fcal value was obtained of 119.769 while the Ftable value was 3.120 thus 119.769 > 3.120, then Ho was rejected and Ha was accepted, meaning that the variables of Location (X1) and Facility (X2) together had a significant effect on Customer Loyalty (Y). The Ttable value is 1.665. By comparing the values of Thcount and Ttable, it can be concluded: the Location variable (X1) with the value of Thcount > Ttable or 4.085 > 1.665 , then Ho is rejected and Ha is accepted. Facility (X2) with a Thcal value of > Ttable or 4,196 > 1,665, then the variables Location (X1) and Facility (X2) have a partial effect on Customer Loyalty (Y) at Cafe Vizie Lahat.